Effects of Crude Palm Oil and Crude Palm Kernel Oil upon Wax Inhibition - Ragunathan, T. (American Chemical Society, 2020)
The ever-increasing demand for the finite source of oil has led oil production companies to produce and transport the produced crude oil as efficiently and economically as possible. One of the major concerns especially in waters like the South China Sea is the deposition of wax on the walls of the pipeline or wellbore, constricting and hindering the hydrocarbon flow. This is due to the low seabed temperatures, which can be below the wax appearance temperature (WAT), leading to the deposition of wax out of waxy crude oil through the molecular dispersion mechanism. Currently, many prevention and remedy methods are in place to overcome the problem, but most of the additives possess environmental threat, as most of the chemical solutions used are toxic, nonorganic, and costly. Hence, this paper aims to provide some insights into the effect of palm oil derivatives such as crude palm oil (CPO) and crude palm kernel oil (CPKO) on wax inhibition. The effect of aging time (i.e., immersion time) was also evaluated. A comparison was made between paraffin inhibition efficiency results (PIE ) obtained by CPO, CPKO, poly(ethylene-co-vinyl acetate) (EVA), and triethanolamine (TEA). It was observed that the average efficiency of 81.67 was obtained when 1 CPO was added to heavy crude oil. The wax inhibition performance reached a plateau after 1.5 h of aging time for all of the investigated samples. Copyright Â© 2020 American Chemical Society.